Dampak Implementasi Kurikulum PAI Terhadap Perilaku Keagamaan - AM Wibowo (Analisa: Journal of Social Science and Religion, 2010)
This study is intended to know the impact of implementing two differentcurricula in Islamic-based senior high schools in Malang, East Java. Usingtwo-way anova method, this study reveals three important facts. Firstly, thereis significantly different religious behaviour of pupils who are taught islamiceducation curriculum from Ministry of National Education from those whoare taught based on the Islamic education curriculum “plus”. Secondly, thereis important difference on religious behaviour of students of the X, XI and XII.The last, the implementation of islamic education in both schools which implementIslamic education curriculum from Ministry of National Education and Islamic  education curriculum “plus” runs well. This study finally arrives at a conclusion that, in terms of religious behaviour,  students of those schools which implement curriculum “plus” are much better than those of the other category.